Sintesis Metil Ester Alginat Dari Rumput Laut (Turbinaria Sp) Dalam Pemanfaatanya Sebagai Stabilizer Makanan - Rico Ramadhan; Rudi Kartika; Subur P Pasaribu (Balai Riset dan Standardisasi Industri Samarinda, 2016)
Esterification of alginic acid obtained from seaweed (Turbinaria sp) extract with methanol (CH3OH) using sulfuric acid catalyst produce methyl ester alginate.The products were confirmed as methyl ester alginate as confirmed by FT-IR spectroscopy. The water content of this product was 11.61% with the pH value 4. The amount of Pb was 0.422 ppm. The viscosity of the product was decreased from 14.67 cps to 12.08 cps with the increasing of the temperature from 27oC to 70oC. The optimum addition concentration of the product was 2% on the ice cream; this value can length the melting point time of the ice cream from 11.19 min to 14.05 min at 31oC.